2011
DOI: 10.1097/ta.0b013e318209589e
|View full text |Cite
|
Sign up to set email alerts
|

Does the Rural Trauma Team Development Course Shorten the Interval From Trauma Patient Arrival to Decision to Transfer?

Abstract: The RTTDC alone and with the embedded communication module significantly reduce delays in the transfer process of the rural trauma patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…There is a great expectation that the course will provide much needed training of care givers in rural institutions and that this should improve trauma care in India. Trauma in rural areas continues to become associated with high mortality not only because of less than ideal training but also because of the dense traffic preventing timely transfer of patients even over short distances to trauma centers for definitive care [10][11][12]. The feeling of isolation among many rural care givers appears to compound the difficulty of providing optimum care for trauma patients because it impedes the communication process between referring and referral personnel-a communication process that should provide the opportunity for dialogue which would promote better care [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a great expectation that the course will provide much needed training of care givers in rural institutions and that this should improve trauma care in India. Trauma in rural areas continues to become associated with high mortality not only because of less than ideal training but also because of the dense traffic preventing timely transfer of patients even over short distances to trauma centers for definitive care [10][11][12]. The feeling of isolation among many rural care givers appears to compound the difficulty of providing optimum care for trauma patients because it impedes the communication process between referring and referral personnel-a communication process that should provide the opportunity for dialogue which would promote better care [11].…”
Section: Discussionmentioning
confidence: 99%
“…Communication issues could be pursued by assessing whether timely communication was established, with satisfaction with this process and its impact on duration of care in the rural centers through questionnaires as was done in the USA [11]. The effect of the PIPS module will be studied by questionnaire requesting information on the frequency of review of patient management, patient outcome, and modification of care based on these sessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Kappel has shown this course to be effective in reducing delays in transfer. 41 One RGH currently provides a similar, bespoke course. 42 CPD relationships with some RGHs and tertiary centres exist to enable rural practitioners to maintain relevant resuscitative and surgical skills.…”
Section: Accepted Manuscript Interfaces With the Widementioning
confidence: 99%
“…The Rural Trauma Team Development Course © (RTTDC), Pre‐Hospital Trauma Life Support (PHTLS), Advanced Trauma Life Support (ATLS ® ), Trauma Nursing Critical Care (TNCC), Advanced Trauma Operative Management (ATOM ® ) and Advanced Surgical Skills for Exposure in Trauma (ASSET) can fill the knowledge gaps, or similar training programmes from the international community as available. Kappel and colleagues8 demonstrated that RTTDC and imbedded communications significantly reduced delays in the transfer process. Shepherd et al 9 showed that helicopter response distances of less than 60 miles (100 km) did not improve the time to definitive care.…”
Section: Introductionmentioning
confidence: 99%